STRATEGY OF INTELLECTUAL MODEL AND BUSINESS INNOVATION TO IMPROVE CREATIVE INDUSTRY COMPETITIVENESS IN MEDAN CITY - Budiarta, Kustoro; Zainal, Andri (Universitas Negeri Medan, 2019)
The aim of this researh is to develop a model of creative industry competitiveness based on the management of intellectual capital strategies (human capital and social capital) and business model innovation and operationally this research aims: 1) to know the human capital model to improve the competitiveness of creative industries in Medan ; 2) knowing the social capital model to improve the competitiveness of creative industries in Medan; 3) knowing the innovation of business models developed to improve the competitiveness of creative industries in Medan City. In this second year (2018), research data will be collected using a valid and reliable questionnaire. Data analysis was carried out in two stages namely descriptive and inferential. The results of this study indicate that: 1). Human capital has a positive and significant effect on social capital with a path coefficient of 0.79; 2). Human capital has a positive and significant effect on business model innovation with a path coefficient of 0.46; 3). Social Capital has a positive and significant effect on business model innovation with a path coefficient of 0.28; 4). Human capital has a positive and significant effect on competitiveness with a path coefficient of 0.59; 5). Social capital has a positive and not significant effect on competitiveness with a path coefficient of 0.04; and 6). Business model innovation has a positive and significant effect on competitiveness with a path coefficient of 0.37. In this case, human capital has the highest value in influencing the competitiveness of the creative industries in Medan.Keywords: Human Capital, Social Capital, Business Model Innovation, Creative Industry Competitiveness, Medan City.